Relationship between H2O2-detoxification, tolerance to H2O2 and virulence of some phytopathogenic bacteria - Künstler, András (Acta Biologica Szegediensis, 2005)
We studied correlation of catalase activity, tolerance to H2O2 and virulence of some phytopathogenic bacteria. Pseudomonas syringae pv. tabaci is a specific pathogen of tobacco. Other pathogenic bacteria, such as Erwinia carotovora, Erwinia chrysanthemi, Agrobacterium tumefaciens can infect a broad spectrum of plant species and there is no plant cultivar resistance against them. We have expected that these bacteria can protect themselves against the unspecific defence actions of plants which involve the accumulation of reactive oxygen species. We demonstrated a high level of catalase activity in a virulent strain of Erwinia chrysanthemi, as compared to a less virulent one. However, we did not find clear correlation between virulence levels and H2O2-detoxifying activity when we examined different bacterial species.